مفهوم الإله الشخصي في وادي الرافدين "صلة الوصل بين عالم الآلهة و عالم البشر" - الصالح عبد الحميد; يوسف رنيم (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
This approach discusses one of the most important ideas which has been brought to us from the ancientIraqian civilization which has been called the (special God). Who is the special God? How (special God) was born? What is his work? And can he change the destiny of people who belong to him? The thinking about being has been interested by man along ages, and that will stay as man stay and as his mind thinks about the existence. Man has tried along Ages to find rest and peace, but the ancient Iraqian civilization hascreated a(special God) who works to give the Iraqian people peace and rest by finding a kind of harmony between the human world and God world. And according to that, man must obey the (special God) and offer him sacrifices. This topic will form the main ideas which will be discussed to takea further step in knowing the ancient Iraqian civilization. يدور هذا البحث حول مفهوم" الإله الشخصي في وادي الرافدين" ذلك الإله الذي كان له دوراً بارزاً و فعالاً في تضييف المسافة بين عالم الآلهة و عالم البشر, و ذلك بقيامه بدور الوسيط بين هذين العالمين: فهو ينقل أوامر الآلهة و رغباتها إلى عالم البشر, و كذلك فهو يحمل أماني و تطلعات الإنسان إلى عالم آلهته. و لكن طبعاً وفق شروط معينة و اتفاق مسبق يعقد بين الطرفين ( الإنسانالرافدي و إلهه الشخصي) : فعلى الإله الشخصي حماية الشخص المنتمي إليه من كل ما يسبب له المصائب أولاً, و التوسط لدى كبار الآلهة ثانياً. و في المقابل يدين الانسان لإلهه الشخصي بالولاء و الطاعة و طبعاً يقدم له القرابين المناسبة. حول هذه الفكرة و وظيفتها سيتركز بحثنا هذا علنا نستطيع إلقاء الضوء على جانب مضيء في الفكر الرافدي القديم.